Virtual archival exhibition system : an authoring tool for developing web-based virtual exhibitions - Ruan, Yang (2010)
This paper describes the design and development of a Virtual Archival Exhibition System (VAES) that facilitates the authoring of web-based virtual exhibitions that can be tailored to serve the needs of various user groups. VAES is a joint collaborative project between the National Archive of Singapore (NAS) and Nanyang Technological University (NTU), Singapore. Based on an XML-based metadata database, VAES provides tools for users to create, update, extract, and search metadata of artifacts and exhibitions stored in the database. The actual digital artifacts (information objects) are reused by referencing as necessary without duplicating the artifacts. Dublin Core (DC) elements and non-DC elements with layered tags are used to describe and provide tailored information of each artifact for different users. In VAES, a virtual exhibition is created based on the pre-defined exhibition metadata and artifact metadata stored in the database. An authoring tool provides a direct manipulation work area for users to browse, display and layout the exhibition page content that is extracted from the database. XML’s Extended Style Sheets (XSL) and Cascading Style Sheet (CSS) are then applied to the layout to yield the final exhibition in HTML format. By using different information layers, reusing the layout setting, and the application of different style sheets, it is easier for authors or archivists, especially for those who are less proficient in IT, to create multiple versions of the same exhibition that vary in content, layout and presentation to meet the varying information needs of a range of different user communities.